Salzburger Kunstverein Jahresbericht 1995. - Salzburger Kunstverein, Salzburg (Salzburg : Salzburger Kunstverein, 1996)
Renner, Lois ; Janin, Zuzanna ; Kurz, Sigrid ; Hammons, David ; Dumas, Marlene ; Ressler, Oliver ; etc.
Duits
boek